Hubungan Antara Daya Ledak Otot dan Kelincahan Terhadap Tendangan Sabit Pada Atlet Perguruan Wahana Mitra Kota Bengkulu - Sari, Piki Permata; Dewi, Citra; Perdima, Feby Elra (UNIVED Press, Universitas Dehasen Bengkulu, 2025)
This study aims to obtain an overview of the extent of the Relationship Between Muscle Explosive Power and Agility to the Ability of the Sickle Kick in Pencak Silat Athletes of Sekolah Wahana Mitra Bengkulu City In accordance with the problems and objectives of the study, this study uses a Quantitative Research method, namely to analyze the relationship between variables using objective theory by applying it through the correlation method. With a population of 38 pencak silat athletes at Sekolah Wahana Mitra Bengkulu City, the research sample was 22 people with a Purposive Sampling sampling technique. The research instruments used in this study were tests and measurements. Data analysis techniques used product moment correlation techniques and Pearson tests with a significance level of 5% and normality tests. Based on the results of field research and the results of data analysis carried out, the results of the muscle explosive power test (vertical jump) showed no significant relationship between the variable of leg explosive power and the ability of the sickle kick. While the results of the agility test (shtulle-run) there was a significant relationship between the variable of agility and the ability of the sickle kick. However, there is a relationship between the variables of leg explosive power and agility to the ability of the sickle kick with a moderate correlation category. It can be concluded that there is a relationship between muscle explosive power and agility to the ability of the sickle kick in pencak silat athletes at Perguruan Wahana Mitra Kota Bengkulu.